Mato Grosso do Sul e Campo Grande: articulações espaço-temporais - Le Bourlegat, Cleonice Alexandre [UNESP] (2000)
The framework of this study was to comprehend the specific conditions surrounding the incorporation and political-economical consolidation of the state of Mato Grosso Sul to the national scenario, during the cyclic evolution of the capitalistic system as well as the role of Campo Grande in this process. The origin and evolution of Campo Grande were analyzed in the context of possible relations between urbanization, regional development and the integration of the state in the national scope. In this approach, several theoretical compatible formulations were considered as to systemic view of reality, from the complex and dynamic point of view. This implies a multi scale reasoning, associating spatial dimension to the historical one, in a theoretical- methodological effort of comprehend the logic between the general and the specific. It was possible to verity peculiarities attributed to Mato Grosso do Sul in the general laws of the capitalistic system, and instances capable of explaning the local effects of the intervention of industrial economy in the dynamic of the process analysed since colonial times, as well as the role of Campo Grande in this process, especially in relation to the economical integration of the state territory to the rest of the nation.